2005
DOI: 10.1177/070674370505001109
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive Steroids in Schizophrenia

Abstract: S chizophrenia is a severe psychiatric disorder that significantly impairs a person's ability to think clearly, manage emotions, make decisions, and relate to others. Many biochemical theories attempt to explain the primary pathophysiological changes in schizophrenia. The DA hypothesis, which postulates hyperdopaminergia in the mesolimbic dopamine system and hypodopaminergia in the mesocortical dopamine system (1), is one of the most popular biochemical theories but is limited by its inability to account for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…This effect can be attributed to a drop in progesterone level (Shulman and Tibbo, 2005). Studies have also reported high progesterone levels in unmedicated chronic patients in response to metabolic stress (Breier and Buchanan, 1992) but normal progesterone levels in medicated early psychosis (Oades and Schepker, 1994) as well medicated chronic schizophrenia patients (Taherianfard and Shariaty, 2004).…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…This effect can be attributed to a drop in progesterone level (Shulman and Tibbo, 2005). Studies have also reported high progesterone levels in unmedicated chronic patients in response to metabolic stress (Breier and Buchanan, 1992) but normal progesterone levels in medicated early psychosis (Oades and Schepker, 1994) as well medicated chronic schizophrenia patients (Taherianfard and Shariaty, 2004).…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 98%
“…Studies have also reported high progesterone levels in unmedicated chronic patients in response to metabolic stress (Breier and Buchanan, 1992) but normal progesterone levels in medicated early psychosis (Oades and Schepker, 1994) as well medicated chronic schizophrenia patients (Taherianfard and Shariaty, 2004). Progesterone has been suggested to act as an endogenous antipsychotic and serve to restore normal functions during the times of stress (Shulman and Tibbo, 2005). Further support for this notion comes from the reports that progesterone metabolite 3a, 5a-THP produces a behavioral profile similar to that of dopamine receptor antagonists by increasing GABAergic tone in rodents (Motzo et al, 1996;Khisti et al, 1998Khisti et al, , 2002.…”
Section: Ovarian Hormones and Human Sensorimotor Gating V Kumari Et Almentioning
confidence: 99%
“…Previous studies have suggested that alterations in cortisol and DHEA-S levels may play a role in the pathophysiology of schizophrenia [3,16,[20][21][22][23]. Serum cortisol and DHEA-S levels may be used as a biological marker for the diagnosis of schizophrenia; however, further studies with larger sample sizes are warranted to support this finding [3].…”
Section: Introductionmentioning
confidence: 94%
“…In addition to the classic effect of steroids on gene transcription via binding to intracellular steroid receptors, neuroactive steroids can alter neuronal excitability via nongenomic effects by acting at inhibitory Gama Amino Butiric Acid A (GABA A ) receptors and/or excitatory NMDA receptors, among others (Shulman and Tibbo 2005), (Marx et al 2006). There is also evidence for a potential role of these neurosteroids in controlling GABA and glutamate release.…”
Section: Neuroactive Steroids Are Neuroprotectivementioning
confidence: 99%